Developing students’ autonomy and responsibility via promoting digital and media literacy in an English-language classroom - Chekhratova, Olena; Kovalenko, Oksana; Petrenko, Virkoriia; Pohorielova, Tetiana; Ved, Tetiana (Amazonia Investiga, 2022)
Digitalization of society necessitates the implementation of new technologies into an educational process on a daily basis, so educators are in constant search for new means of facilitating this process and should consider the challenges of a digital world. The paper hypothesizes the idea that by improving students’ digital and media literacy using self and peer assessment techniques in blended learning, the effectiveness of the educational process will increase along with the development of students’ responsibility and autonomy. To prove the assumed idea a research has been conducted with the students enrolled into the educational process of Simon Kuznets Kharkiv National University of Economics (Ukraine). In the paper an alternative assessment method based on interrelation between students’ digital and media literacy and their autonomy and responsibility is offered to be implemented in the English-language classroom.